2017
DOI: 10.1108/ijpdlm-03-2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

The impact of product complexity and variety on supply chain integration

Abstract: Purpose The purpose of this paper is to examine the antecedents of supply chain integration (SCI) at the product level. More specifically, it aims to show the relationship between product-level characteristics (i.e. product complexity and product variety) and different dimensions of SCI (i.e. internal, supplier and customer integration). Design/methodology/approach A survey-based research design is developed to measure different dimensions of SCI, product complexity and product variety. The authors use struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 92 publications
(127 reference statements)
13
59
0
1
Order By: Relevance
“…It has been observed that integrated green supply chain results in operational performance of the focal firm (Shou et al, 2017;Khan et al, 2008). Khan et al (2008) further discussed that the product design supply interface contributes to better integration to make the supply chain management smooth.…”
Section: Product Variety and Integrated Green Supply Chain Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that integrated green supply chain results in operational performance of the focal firm (Shou et al, 2017;Khan et al, 2008). Khan et al (2008) further discussed that the product design supply interface contributes to better integration to make the supply chain management smooth.…”
Section: Product Variety and Integrated Green Supply Chain Managementmentioning
confidence: 99%
“…Content validity was ensured with a careful assessment of the scale items adopted from previous studies (Shou et al, 2017;Khan et al, 2008;Jacobs et al, 2007;Bortolotti et al, 2013). A pre-test was conducted with expert opinions of two academic scholars from two universities of Sri Lanka for face validity and a pilot test was carried for 30 respondents of merchandisers in the apparel sector.…”
Section: Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Supply chain integration refers to the degree to which an organization's activities are integrated with the activities of its suppliers, customers, and other firms in its supply chain [1]. Due to the gradual increase of outsourcing business proportion, the globalization of the supply chain and the shortening of the product life cycle, the production and operation activities of enterprises begin to face higher risks [9].…”
Section: Connotation Of Supply Chain Integrationmentioning
confidence: 99%
“…Supply chain integration refers to the degree to which an organization's activities are integrated with the activities of its suppliers, customers, and other firms in its supply chain [1]. Integration makes the upstream, middle and downstream enterprises reach to the logistics enterprises.…”
Section: Introductionmentioning
confidence: 99%